Development and Validation of Religious Sectarian Intolerance Scale for Muslim Adults in Pakistan - Shahzad, Nimrah (Journal of religion and health, 2022)
Religious sectarian intolerance occurs when members of different religious sects within a faith are unable to tolerate the religious beliefs and practices of each resulting in bigotry and prejudice toward each other. The present research sought to develop a psychometrically sound measure of religious sectarian intolerance for Muslim adults. The research comprised two studies. Study I involved the development of an initial item pool for the Religious Sectarian Intolerance Scale (RSIS). The initial pool of items was based on thematic analysis from focus group discussions. This item pool was reviewed by a committee of experts resulting in a 39-item initial draft of the RSIS, which was administered to a purposive sample of Pakistani Muslim adults (N = 270). The exploratory factor analysis revealed a four-factor structure for the RSIS (with loadings ranging from 0.56 to 0.94) that explained 62% of the variance. The factors include dogmatic loyalty (9 items), social intolerance (13 items), renunciation of other religious Sects. (8 items), and propagation of one's Sect. (9 items). All factors were moderately related to each other with acceptable Cronbach's alpha (.78 to .92). Study II replicated the factorial structure of RSIS through confirmatory factor analysis on an independent sample of Muslim adults (N = 274). The convergent validity of the RSIS was demonstrated by a positive relationship with dogmatism. Overall, the findings indicated that the RSIS is a psychometrically sound measure that provides a standard operationalization for religious sectarian intolerance in Muslim cultures and it needs to be studied further in Muslim populations across the globe.